Neurosonological Diagnosis in the Acute Phase of Stroke is a Sign of Qualified Care - Schlachetzki, Felix; Nedelmann, Max; Poppert, Holger; Saur, Dorothee; Harloff, Andreas; Liman, Jan; Reinhardt, Matthias; Stolz, Erwin; Kaps, Manfred (Neurology International Open, 2017)
Ultrasonography of the extra- and intracranial vessels has been an essential part of the approved concept of stroke units in Germany. This review aims to highlight unique selling points of neurosonology in the acute phase of stroke.In acute ischemic stroke, occlusion or stenosis of an arterial segment induces individually variable and complex changes in cerebral hemodynamics. Acute arterial occlusion may persist, may partially or completely recanalize, re-occlude after initial recanalization or may be compensated by collateral blood flow. Ultrasonography is most suitable to monitor these hemodynamic changes in the early stages of a stroke. The earlier neurosonography is performed, the better the pathophysiological understanding is, and the more targeted are therapeutic efforts to limit acute neurovascular injury. A general view is that CT angiography and/or magnetic resonance imaging and neurosonographical techniques in acute stroke care are competitive and interchangeable. However, these methods are rather complementary since the visualization of blood vessels, cerebral perfusion and hemodynamic flow is based on different physical principles. Each method has particular advantages and limitations. With respect to the specific diagnostic question, one method or the other may be indicated. It is the responsibility of the treating neurologist to select the most appropriate imaging method and to provide specific competence in neurosonography. The main scope of this article is to motivate neurologists to apply neurosonography specifically in the acute phase of stroke in order to get an independent assessment and unique hemodynamic information instead of leaving neurovascular competence to radiologists. Purposeful use of neurosonologic techniques makes the difference in high quality stroke care.